TAHAPAN PADA PROGRAM PENYEDIAAN RUMAH BERBASIS MASYARAKAT - Barimbing, Herbet; Anugrahini, Triyanti (UI Scholars Hub, 2021)
Inadequate houses and slums are part of the welfare problems of low-income families. A community-based approach is believed to be an effective way of providing housing for low-income families, as it is seen as an effort to empower them. This study describes the stages in community based housing program in Mauk Sub district, Tangerang District, conducted by a non-governmental organization, Habitat for Humanity Indonesia (HFH Indonesia). This study aims to describe how the stages being implemented with the community based approach. This qualitative research using purposive sampling techniques. Data collected with a semi- structured in-depth interview with the representatives of the local leaders in Mauk, representatives of local committee, representatives of HFH Indonesia staff, and representatives of Mauk’s community members. This study found that the program carried out in 6 stages, namely: Survey and Assessment, Local Committee Formation, Home Partner Selection, Social Preparation, Program Implementation, Monitoring, and Evaluation. HFH Indonesia has been implementing the community based approach in its program as an effort to empower the community. Yet, the study revealed there is need a termination phase as a part of the program sustainability. In this phase, the local committee needs to be officially and legally institutionalized, and capacity building to be a Community Based Organization. This study also confirmedthat the housing provision program for the low income families need to be carried out with the community based approach which implemented community participation and building the community’s capacities in order to empower and enable them to solve their housing problem(s) with their own resources and capacities. This study also revealed that if there is not any local organization partner as the community workers in the particular program area, then it can start with the local committee formation.